Exploring TVET Institution Directors’ Barriers in Managing Malaysian TVET Institutions-Industry Partnership - Mohamad, Norazlinda; Mohd Affandi, Haryanti; Sohimi, Nurul Eizzaty; Mustaffa Kamal, Mohd Firdaus; Moreno Herrera, Lazaro; Zulkifli, Rabihah Munirah; Abas, Nor Haslinda (Journal of Technical Education and Training, 2023)
For developing nations to meet the demand for skills in the twenty-first century, TVET is essential. The TVET institution actively creates a skilled workforce to meet the needs of the nation’s labour market to meet those demands. As a result, efforts are being made to improve the existing TVET institutions. This study looked into the difficulties faced by TVET institution managers when handling their relationships with collaboration. The quantitative approach used in this study was the survey design approach. The right respondents are chosen for this study using purposeful sampling techniques. A total of 53 directors of TVET institutions in Malaysia and 30 representatives from industry were chosen as respondents for this study. The Rasch measurement model was used to analyze the data. This study identified managerial skills and common barriers as the two main obstacles to the collaboration between Malaysian TVET institutions and industries. Technical, human, and conceptual skills are the three categories used to categorize managerial skill barriers. Technically, directors are unable to put knowledge into practice because they lack computer proficiency, managerial knowledge and experience, and methods and techniques for performance monitoring tools. Conceptually, directors struggle to plan long-term objectives, articulate strategies and comprehend the organizational structure of their industry. Finally, directors lack the ability to manage relationships between organizations and the drive to launch partnerships with the sector. While this was going on, the common TVET institution-industry collaboration barriers were grouped into four categories: governance issues, funding and financial issues, management issues in collaboration, and industry-institution culture issues.